Effects of Fat Replacement by Pectin from Dragon Fruit Peels on Physicochemical Properties of Salad Dressing - Sakkaekaew, Korawit; Pasukamonset , Porntip; Siriwong , Nongnuch (Dusit Thani College Journal, 2020)
This research aimed to study the fat replacement with pectin from dragon fruit peels on physicochemical properties of salad dressing by studying the appropriate ratio of pectin as a fat replacer in salad dressing for 4 levels: 0% (control formula), 0.68%, 1.36% and 2.04%. Sensory characteristics, physicochemical properties such as color (L*, a* and b*), viscosity, rheological properties, pH, and peroxide values as well as nutritional values of salad dressing replaced with pectin from dragon fruit peels were evaluated. The results showed that pectin affects the consumer acceptance, physicochemical properties, and nutritional value of salad dressing. When increase the contents of pectin, b* value, viscosity and pH value decreased. Moreover, rheological properties and a* value increased (p <0.05). There was no change in peroxide value of salad dressing when replaced pectin at P 25 and P 50 level. The energy and fat composition of salad dressing was significantly decreased (p <0.05) as the ratios of pectin increased. Salad dressing with pectin replacement at 1.36% showed the highest acceptance. Therefore, the use of pectin for fat replacement in salad dressing products would be good for consumers. This study has shown the possibility of applying pectin as a fat replacer in salad dressings.